2013
DOI: 10.1016/j.eururo.2012.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-generation Sequencing of Advanced Prostate Cancer Identifies Potential Therapeutic Targets and Disease Heterogeneity

Abstract: Background Most personalized cancer care strategies involving DNA sequencing are highly reliant on acquiring sufficient fresh or frozen tissue. It has been challenging to comprehensively evaluate the genome of advanced prostate cancer (PCa) because of limited access to metastatic tissue. Objective To demonstrate the feasibility of a novel next-generation sequencing (NGS) based platform that can be used with archival formalin-fixed paraffin-embedded (FFPE) biopsy tissue to evaluate the spectrum of DNA alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
369
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(379 citation statements)
references
References 24 publications
8
369
1
1
Order By: Relevance
“…The data were subjected to exponential growth-curve analysis constrained to share an initial value and to 2-way ANOVA analysis followed by Bonferroni's multiple comparisons test. Significant differences as compared with the vehicle-treated control group (P < 0.05) were detected only for seviteronel at a dose of 100 mg/kg (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The data were subjected to exponential growth-curve analysis constrained to share an initial value and to 2-way ANOVA analysis followed by Bonferroni's multiple comparisons test. Significant differences as compared with the vehicle-treated control group (P < 0.05) were detected only for seviteronel at a dose of 100 mg/kg (days [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Methodsmentioning
confidence: 97%
“…In addition to enhanced AR expression, there is considerable evidence to suggest that mutations in the AR that alter its response to pharmacological agents may also be important in CRPC (6,21,23). Specifically, treatment failure in patients progressing while on antiandrogens has been attributed to point mutations in the AR: flutamide, T877A; bicalutamide, W741C; and enzalutamide, F876L (6,21,(24)(25)(26)(27).…”
Section: Cyp17 Inhibitors Directly Bind and Antagonize Ar Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal expression patterns of β-catenin have been observed in 20-71% of prostate cancer samples (51)(52)(53), and high levels of β-catenin are concomitantly associated with increasing Gleason score and castration resistance (53,54). Although recent studies showed that mutations in allophycocyanin and β-catenin can be detected in approximately 10% and 12% of castrationresistant prostate cancer, respectively (55)(56)(57), it seems that Wnt/ β-catenin signaling could play a more common role in prostate cancer than would be predicted by the point mutation rates of these downstream effectors (53,58,59). Alterations in Wnt ligands and their modulators that are secreted from prostate epithelia and the surrounding stroma may serve as the alternative mechanism for activation of Wnt signaling in a subset of human prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a high rate of deletion or methylation of either ATM or MCPH1, a proximal regulator that recruits ATM to the sites of DNA DSBs, was reported in breast cancer samples (96%, 121 of 126). In prostate cancer, targeted next-generation sequencing has revealed an 8% incidence of ATM mutations (59). ATM is also one of the most commonly mutated genes in pancreatic cancer (60) or lung adenocarcinoma (61).…”
Section: Somatic Atm Mutations In Cancermentioning
confidence: 99%